Fusion of Geo-Referenced Data for Visual Simulation in Location-based Mobile Computing - Calado, A.; Dias, J. (Proceedings of Conference on Construction Applications of Virtual Reality 2004, CONVR 2004, ADETTI/ISCTE, Lisbon, 2004)
Mobility is an emerging concept in the GIS (Geographic Information Systems) domain, and according to some specialists, it will introduce a revolution in how GIS users interact with their data. With this paper, we propose a system architecture for a global, fully mobile and location-based GIS system, creating an abstraction to support generic multi-level geo-referenced data, from satellite imagery, airborne imagery, GIS mapping, 3D volumetric models and augmented reality, with multiple levels of detail, as well as multiple forms of visualization and interaction.